Upregulation of miR-345-5p suppresses cell growth of lung adenocarcinoma by regulating ras homolog family member A (RhoA) and Rho/Rho associated protein kinase (Rho/ROCK) pathway - Qiao-Yun Zhou (Wolters Kluwer, 2021)
Abstract. Background:. Microribose nucleic acids (miRNAs) are implicated in the progression of lung adenocarcinoma. MicroRNA-345-5p (miR-345-5p) is a recently identified anti-oncogene in some human cancers, but its functional role and possible molecular mechanism in lung adenocarcinoma remain unknown. This study aimed to identify the biological function and underlying mechanism of miR-345-5p in lung adenocarcinoma cells. Methods:. In this study, lung adenocarcinoma tissues and adjacent tissues were collected in the First Affiliated Hospital of Anhui Medical University between April 2016 and February 2017. The expression of miR-345-5p and ras homolog family member A (RhoA) in lung adenocarcinoma tissues and human lung adenocarcinoma cell lines (A549, H1650, PC-9, and H441) was detected by reverse transcription quantitative polymerase chain reaction analysis. Functional assays including colony formation, flow cytometry analysis, wound healing, and transwell assays were performed to assess the proliferation, apoptosis, migration, and invasion of lung adenocarcinoma cells. In addition, RNA pulldown and luciferase reporter assays were conducted to evaluate the relationship between miR-345-5p and RhoA. Difference between the two groups was analyzed with Student's t test, while that among multiple groups was analyzed with one-way analysis of variance. Results:. MiR-345-5p expression displayed lower level in lung adenocarcinoma tissues (0.241 ± 0.095 vs.1.000 ± 0.233, t = 19.247, P < 0.001) and cell lines (F = 56.992, P < 0.001) than control tissues and cells. Functional experiments demonstrated that upregulation of miR-345-5p inhibited the malignant phenotypes of lung adenocarcinoma cells via suppressing cell proliferation, migration, invasion, and facilitating cell apoptosis. Additionally, RhoA was verified to be the downstream target of miR-345-5p. Expression of RhoA was downregulated by overexpression of miR-345-5p in PC-9 (0.321 ± 0.047 vs. 1.000 ± 0.127, t = 8.536, P < 0.001) and H1650 (0.398 ± 0.054 vs. 1.000 ± 0.156, t = 4.429, P = 0.011) cells. Rescue assays revealed that overexpression of RhoA rescued the suppressive effects of miR-345-5p upregulation on proliferation, migration, and invasion of lung adenocarcinoma cells. Further, miR-345-5p was found to regulate the Rho/Rho-associated protein kinase (ROCK) signaling pathway by downregulation of RhoA in lung adenocarcinoma cells. Conclusions:. MiR-345-5p plays a tumor suppressor role in lung adenocarcinoma cells by downregulating RhoA to inactivate the Rho/ROCK pathway.